Assessment of dietary patterns, physical activity levels, and sedentary lifestyle in adolescents from an urban high school - Lecina-Monge, Miguel A; Asín-Izquierdo, Iván; Gómez-Carmona, Carlos D; García-Gimenez, Alejandro (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This quantitative cross-sectional study evaluated nutritional habits, physical activity levels, and sedentary behaviors in 62 students in 4th grade of secondary education (15.44±0.62 years) from a public high school in Zaragoza, Spain. Results showed that students consumed an average of 1.98±1.42 servings of fruit and 2.05±1.61 servings of vegetables daily, with higher intake of meat (2.00±1.24) than fish (1.00±1.21). Gender differences were found (p<0.05): males consumed more meat while females ate more vegetables and practiced voluntary fasting more frequently. On average, students engaged in physical activity 3.15±2.62 days per week, with males being significantly more active. Screen time was considerable (1.52±0.88 hours TV; 2.73±1.34 video games). Correlations revealed positive associations between physical activity and healthy food consumption (r>0.39), while sedentary behaviors were related to unhealthy foods (r>0.43). These findings suggest the need for specific interventions that promote healthy habits within the school environment.